The characteristic changes of betung bamboo (Dendrocalamus asper) pretreated by fungal pretreatment - Widya Fatriasari; Wasrin Syafii; Nyoman J Wistara; Khaswar Syamsu; Bambang Prasetya (International Journal of Renewable Energy Development, 2014)
The fungal pretreatment effect on chemical structural and morphological changes of Betung Bamboo was evaluated based on its biomass components after being cultivated by white rot fungi, Trametes versicolor. Betung bamboo powder (15 g) was exposed to liquid inoculum of white rot fungi and incubated at 270C for 15, 30 and 45 days. The treated samples were then characterized by FT-IR spectroscopy, X-Ray diffraction and SEM-EDS analyses. Cultivation for 30 days with 5 and 10% loadings retained greater selectivity compared to that of the other treatments. FTIR spectra demonstrated that the fungus affected the decreasing of functional group quantities without changing the functional groups. The decrease in intensity at wave number of 1246 cm-1 (guaiacyl of lignin) was greater than that at wave number of 1328 cm-1 (deformation combination of syringyl and xylan) after fungal treatment. X-ray analysis showed the pretreated samples had a higher crystallinity than the untreated ones which might be due to the cleavage of amorphous fractions of cellulose. The pretreated samples have more fragile than the untreated ones confirmed by SEM. Crystalline allomorph calculated by XRD analysis showed that fungus pretreatment for 30 days has transformed triclinic structure of cellulose to monoclinic structure.